Physiotherapy in multiple sclerosis - Łuszczyńska, Anna; Kuliński, Włodzisław (Medical Studies/Studia Medyczne, 2015)
Introduction: Multiple sclerosis (MS) is a chronic, progressive, demyelinating disease of the central nervous system. 2.5 million people are affected by MS worldwide; in Poland, the number of patients is approximately 40,000. Patients with multiple sclerosis suffer from a number of symptoms associated with this disease. Aim of the research: To assess the effectiveness of physiotherapy in MS. Material and methods : The study enrolled 25 MS patients aged 27–72 years (including 16 females and 9 males), undergoing 6-week rehabilitation. They were examined twice: before and after rehabilitation. The study used two questionnaires created by the author. Evaluation of the clinical status and disease severity was based on the Kurtzke Expanded Disability Status Scales (EDSS), the Lawton Instrumental Activities of Daily Living (IADL) Scale, and the Multiple Sclerosis Impact Scale (MSIS-29). The results were analysed with Student’s t-test and the chi-square (χ 2 ) test. Results : Statistical analysis showed significant (the level of significance was 0.05) progress in the functional status of the patients after physiotherapy, as evidenced by improved results with respect to the motor efficiency in the Kurtzke Expanded Disability Status Scale (EDSS), the functional assessment in the Lawton Instrumental Activities of Daily Living (IADL) Scale, and the influence of MS on patients’ daily life in the Multiple Sclerosis Impact Scale (MSIS-29) seen in the majority of the patients, which confirms a positive impact of the therapy. Conclusions: In the study group, comprehensive rehabilitation had a beneficial influence on the improvement of functional status and the level of motor ability. Physiotherapy turned out to be an extremely effective form of symptomatic treatment of MS patients.